Curbside consultation in uveitis 49 clinical questions - Foster, C. Stephen 1942-; Opremcak, E. Mitchel.; Hinkle, David M. (Curbside consultation in ophthalmology series., 2012)
"Are you looking for concise, practical answers to those questions that are often left unanswered by traditional references on uveitis? Are you seeking brief, evidence-based advice for the daily examination of patients? Curbside Consultation in Uveitis: 49 Clinical Questions provides quick and direct answers to the thorny questions most commonly posed during a "curbside consultation" between experienced clinicians. Dr. Stephen Foster has designed this unique reference in which uveitis specialists offer expert advice, preferences, and opinions on tough clinical questions commonly encountered by ophthalmologists, residents, and other health care professionals. The unique Q&A format provides quick access to current information related to uveitis with the simplicity of a conversation between two colleagues. Images, diagrams, and references are included to enhance the text and to illustrate clinical diagnoses and treatment plans. Curbside Consultation in Uveitis: 49 Clinical Questions provides information basic enough for residents while also incorporating expert pearls that even high-volume ophthalmologists will appreciate. Refractive surgeons, general ophthalmologists, and residents alike will enjoy the user-friendly and casual format. "--